Use of Technology in Increasing the Effectiveness of Class Management at Madrasah Ibtidaiyah Negeri 3 Jember - Hilda Yulianti; Mukni’ah Mukni’ah; Ervan Iswanto (Aksara Shofa, 2024)
This research aims to delve into and further analyze the utilization of technology as a means to enhance the effectiveness of classroom management in the environment of Madrasah Ibtidaiyah Negeri 3 Jember. The methodology employed in this study is qualitative with a case study approach, allowing researchers to thoroughly explore details regarding the use of technology in the context of classroom management. Data collection is conducted through various methods, including observation, interviews, and document analysis, to gain a profound understanding of the optimal implementation of technology in class management. Through this research, it is anticipated that findings will provide in-depth insights and relevant recommendations for stakeholders, with the ultimate goal of improving the quality of education at Madrasah Ibtidaiyah Negeri 3 Jember. These findings are expected to serve as a foundation for the development of strategies and policies focusing on the enhancement of efficiency and effectiveness in classroom management through technology integration, thereby significantly impacting students' learning experiences and the overall progress of education in the madrasah.